The Effect of Debit, Credit and BI-RTGS Card Usage on Indonesia's Economic Growth - Anugrah, Johan; Izharuddin, Izharuddin (Asian Journal of Management Analytics, 2025)
This study aims to analyze the effect of debit, credit and BI-RTGS card usage on economic growth in Indonesia using secondary data from 34 provinces in Indonesia in the period 2019 to 2023. This study uses the panel data linear regression analysis method with the E-views application to process data. The dependent variable used is Gross Regional Domestic Product (GRDP), while the independent variables include debit card usage, credit card usage and Bank Indonesia Real Time Gross Settlement (BI-RTGS) transactions. The results showed that debit card usage, credit card usage and BI-RTGS significantly affect GRDP in Indonesia. The government needs to continue to support the development of non-cash payment systems as an effort to encourage economic growth.